Digital Storytelling as a Teaching Medium in Reading Classroom - Anggeraini, Yentri; Afifah, Nurul (Universitas Negeri Semarang, 2017)
As we know that teaching reading of short stories is to make students more understand about the material and can analyze the contents of the story including the moral value, plot, setting, and characters in the story. The objective of this study were to find out (1) what the students` initial condition on reading short stories texts before using the developed digital storytelling are, (2) how the digital storytelling developed for teaching reading of short stories students at English education study program university of Baturaja is, (3) how effective the developed digital storytelling used for teaching reading of short stories is. The result of this study was this digital storytelling was developed on the basis of questionnaire results and interview result. it was found that the media of digital storytelling should cover the need of the students which has some criteria such as after reading the short stories hopefully they can increase their vocabulary, they like to read dramatic and romantic story, the suitable medias in learning reading of short stories are online reading sources and video, kinds of digital storytelling are video words and digital storytelling video clips, digital storytelling should be easy to operate and the comfortable digital storytelling is to have more voice and sound. The students revealed this improvement after applying digital storytelling for teaching reading of short stories. The materials development brings improvement on the students` scores and it can rise their interest in reading short stories.